Hendra Gunawan HUBUNGAN KEPATUHAN MINUM OBAT PADA ODGJ DENGAN KEKAMBUHAN PASCA RAWAT DIWILAYAH KERJA UPT PUSKESMAS LUBUK LANDAI TAHUN 2023: HUBUNGAN KEPATUHAN MINUM OBAT PADA ODGJ DENGAN KEKAMBUHAN PASCA RAWAT DIWILAYAH KERJA UPT PUSKESMAS LUBUK LANDAI TAHUN 2023 - Gunawan, Hendra; Dwiaini, Ita; Enopadria, Costarin (Lembaga Marwah Rakyat, 2024)
Compliance with taking medication is the main thing that influences the success of treatment and recovery in schizophrenia patients. Post-treatment recurrence of ODGJ patients is still a serious concern for families and health workers. The methodology in this research is to look at the relationship between medication adherence in ODGJ patients and post-treatment recurrence rates using a cross-sectional research design. The research sample was post-treatment ODGJ patients with a sample size of 41 people. The research results showed that almost half of ODGJ had a level of medication adherence in the quite good category, 43.9% (18 people). Post-treatment recurrence in ODGJ was mostly in the frequent recurrence category, 58.5%. The results of chisquare analysis showed no relationship between medication adherence in ODGJ patients and post-treatment recurrence rates. The suggestion is that research needs to be carried out by looking at several dominant factors in the recurrence rate of ODGJ patients after treatment Keywords: Schizophrenia, Compliance with taking medication